A mono-metallic Pd(ii)-cage featuring two different polar binding sites. Issue 5 (19th December 2018) - Escobar, Luis; Villarón, David; Escudero-Adán, Eduardo C.; Ballester, Pablo
Abstract : A tetra-α super aryl-extended tetra-pyridyl calix[4]pyrrole self-assembles into a mono-Pd(ii ) cage featuring two different and converging polar binding sites. Abstract : The tetra-α isomer of a super aryl-extended tetra-pyridyl calix[4]pyrrole self-assembles into a mono-metallic Pd(ii )-cage featuring two different and converging polar binding sites. Mono- and di-topic polar guests are bound reversibly in the cage. A mechanism for guest exchange in the cage complexes is proposed.